Certified Quantum Randomness with Coherent Detection - Sena, Vitor L.; Alves, Moisés; Zamora, Santiago; Sarubi, Tailan S.; Oliveira Junior, Alexssandre de; Tacla, Alexandre B. (Anais do Workshop de Redes Quânticas (WQuNets); 2026: Anais do III Workshop de Redes QuânticasDO - 10.5753/wqunets.2026.23540, 2026)
In this work, we analyze a semi-device-independent technique for quantum random number generation (QRNG) certification based on coherent detection. We consider a prepare-and-measure scenario, in which pure quantum states are prepared and sequentially measured using homodyne detection, a continuous-variable measurement, and evaluate dimension witness (DW) inequalities to certify quantum randomness. We extend the DW framework to this continuous-variable setting through phase-space binning optimization and demonstrate that symmetric binning maximizes DW violation across single-, double-, and triple-partition configurations. We additionally explore heterodyne (double homodyne) detection as a complementary coherent measurement; no witness violation is observed under this scheme for several discretization schemes. This work provides additional analysis to the study of certifiable QRNG based on homodyne detection, a mature and widely available technology with natural applicability in secure network communications.